Diagnostic Challenges in Fungal Coinfections Associated With Global COVID-19 - Ariyo Shahin Jafari; Amir Sasan Mozaffari Nejad; Hossein Faraji; Ahmed S. Abdel-Moneim; Saeme Asgari; Hakime Karami; Ali Kamali; Ali Asghar Kheirkhah Vakilabad; Ali Habibi; Motahareh Faramarzpour (Scientifica)
The early diagnosis of opportunistic infections is a critical concern for patient care worldwide, particularly in the context of the COVID-19 pandemic. This review examines the challenges and advancements in the management and early diagnosis of opportunistic fungal infections, which have become increasingly prominent during the pandemic. Using multiple sources, including curated databases such as PubMed and Scopus, as well as Google Scholar for broader literature searches, we systematically reviewed studies on COVID-19-associated fungal infections, with a focus on candidiasis, mucormycosis, and aspergillosis. The inclusion criteria encompassed peer-reviewed articles, clinical case reports, and cohort studies that discussed diagnostic methods, clinical outcomes, and treatment responses. Data were systematically extracted and analyzed to identify key trends and gaps in current diagnostic practices. Given the significance of opportunistic fungal infections—particularly the selected species—this review provides a comprehensive analysis of diagnostic challenges and advancements in the context of COVID-19 and beyond. Currently, there is no definitive strategy for effectively addressing these opportunistic pathogens, highlighting the need for continued research and innovation. Despite advancements in medical technology, opportunistic fungal infections continue to pose significant challenges to early and accurate diagnosis. The COVID-19 pandemic has exacerbated these challenges, with secondary fungal infections contributing to increased morbidity and mortality rates. This review highlights the complexities of diagnosing fungal coinfections and emphasizes the urgent need for improved diagnostic strategies. Enhancing the early and accurate detection of these infections is critical for effective patient management, particularly during viral pandemics. Addressing the challenges outlined in this review requires innovative diagnostic approaches to improve patient outcomes and reduce the burden of opportunistic infections on global healthcare systems.